VOICE AS A PROFESSIONAL INSTRUMENT IN THE ACTIVITY OF PHYSICAL EDUCATION TEACHER - Igor Arsene; Gheorghiu Aurelian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
The content of this article highlights the issue of the voice as a professional tool in the activity of the physical education teacher. The correlation relationship between the particularities of the voice and the teacher's perception of implementing the voice as a professional tool in his activity is highlighted. The voice, as a professional instrument, becomes strong, mobile, flexible, sound, has a wide range and creates an atmosphere of mutual understanding among the participants in the educational process. In the professional community, it is necessary to form a clear idea that the voice is not the property of any science - phoniatrics, voice pedagogy, speech therapy, etc.